An Design of AI based leave scheduling and managing Application - Pathan, A.I; Nayak, Bhavnashri; Nayak, Bhagyashri; Dhatrak, V.B; Daivat, A.K (International Journal of Computer Sciences and Engineering, 2020)
The online Staff Leave Management System is used to automate the process of leave applications and their approvals. It mainly deals with details of all institutional staff both teaching and non-teaching of various departments and also their leave maintenance. A staff can submit a leave application after verifying his/her current leave balances which will be shown by based on status module. The HOD and Principal verifies the submitted leave and checks the available leave balances for accepting or rejecting the leave. Admin will generate the report for leave management of staff. This system is being developed to convert a traditional process of leave management into automated system that can be process by android devices, where multi-user access is allowed. The AI based system will work with AI to find the available staff for the possible load adjustment from time schedule.